Responsible Investment: Taxes and Paradoxes - Reijo Knuutinen; Matleena Pietiläinen (De Gruyter, 2022)
Taxes have become an issue of corporate social responsibility (CSR), but the role of taxation is to some extent an ambiguous and controversial issue in the CSR framework. Similarly, another unclear question is what role investors who are committed to sustainable and responsible investment (SRI) see taxes as having on their environmental, social, and governance (ESG) agenda. Corporate taxes have an inverse relationship with the return of the investors: taxes paid directly affect what is left on the bottom line, reducing the return of investors. Furthermore, investors are now more aware of tax-related risks, which can include different forms of reputation risk. Corporate tax planning may increase the returns, but those increased returns are riskier. This study focuses particularly on the relationship between SRI and taxation. We find that tax matters are considered to be on the ESG agenda, but their role and significance in the ESG analysis is unclear.